Investigating the Correlation Among Chinese EFL Teachers' Self-efficacy, Work Engagement, and Reflection - Han, Yawen; Wang, Yongliang (Frontiers in Psychology, 2021)
As the forerunners of education, teachers and their psycho-affective variables have been the focus of numerous studies in the past decades. To add to this line of inquiry, the present study aimed to scrutinize the correlation among English as a foreign language (EFL) teachers' self-efficacy, work engagement, and reflection in the context of China. To do so, three previously validated questionnaires related to each of the variables were distributed among Chinese EFL teachers with various experiences and academic degrees, and a sample of 614 completed the questionnaires. The results of Pearson's Product-moment correlation revealed that the participants' self-efficacy, work engagement, and reflection were positively correlated. Moreover, the results of regression analysis and ANOVA demonstrated that Chinese EFL teachers' self-efficacy and work engagement significantly predicted their reflection. The findings have viable takeaways for EFL teachers and teacher education programs in that they can invest more time and energy in promoting psychological factors in teaching the English language along with pedagogical issues.